Clozapine impact on FosB/ΔFosB expression in stress preconditioned rats: response to a novel stressor - Osacka Jana (Sciendo, 2019)
Objective. Prolonged treatment with neuroleptics has been shown to induce FosB/ΔFosB expression in several brain regions including the medial prefrontal cortex, dorsomedial and dorsolateral striatum, ventrolateral and dorsolateral septum, nucleus accumbens shell and core, and the hypothalamic paraventricular nucleus (PVN). Some of these regions are known to be also stress responsive. This study was designed to determine whether repeated clozapine (CLZ) administration for 7 consecutive days to Wistar rats may modify FosB/ΔFosB expression in the above-mentioned brain areas induced by acute stress or novel stressor that followed 13-day chronic mild stress preconditioning.